Effectiveness of different bases of support during Y-raise exercises on upper and lower trapezius electromyographic activity in healthy male subjects - Su-Yeon Bae; Tae-Hyeong Kim; In-Cheol Jeon (Journal of Men's Health)
Background: Y-raise exercise (YE) is often recommended as an effective intervention for increasing lower trapezius (LT) muscle activation. Methods: 15 healthy males were asked to perform YE with different bases of support while lying prone: YE, YE on a Togu jumper (YET) and YE on a foam roller (YEF) in random order. Upper trapezius (UT) and LT activities were measured using surface electromyography during three different exercises. One-way repeated analysis of variance and Bonferroni post hoc test were used to compare the muscle activities. The significance level was set at α = 0.017. Results: The muscle activity of LT and the ratio of LT/UT muscle activity were significantly different among three different exercises (YE, YET, YEF) (adjusted p-value (padj) < 0.017). The muscle activity of LT was higher during the YEF than the YE and YET (padj < 0.017). The LT/UT muscle activity ratio during the YEF was higher than the YE (padj < 0.017). Conclusions: YEF can be recommended to selectively enhance LT activation and improve the LT/UT activity ratio in healthy male subjects.